2018
DOI: 10.5435/jaaosglobal-d-17-00035
|View full text |Cite
|
Sign up to set email alerts
|

Irreducible Dislocation of the Radial Head Associated With Pediatric Monteggia Lesions

Abstract: Background:In pediatric patients with Monteggia lesions, the radial head can be reduced manually when displacement of the fractured ulna is corrected. Occasionally, however, a dislocated radial head could not be reduced manually even when the length and/or angulation of the fractured ulna had been corrected. We can find such cases in the literature, but those are single case reports. We encountered 17 cases of irreducible dislocation of the radial head in pediatric Monteggia lesions during the past 43 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…[ 19 ] Clinically, the diagnostic standards of Monteggia fracture are the humeral lateral line on the anteroposterior plate and the long axis of radial shaft on the lateral plate. [ 20 , 21 ] On ultrasound, the subluxation is obvious and there is usually annular ligament incarceration in radio-capitellum joint, the normal “double-hump sign” and “congruency sign” disappeared (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Clinically, the diagnostic standards of Monteggia fracture are the humeral lateral line on the anteroposterior plate and the long axis of radial shaft on the lateral plate. [ 20 , 21 ] On ultrasound, the subluxation is obvious and there is usually annular ligament incarceration in radio-capitellum joint, the normal “double-hump sign” and “congruency sign” disappeared (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…For clinical cases requiring open operative intervention for the radial head dislocation, the most noted block to anatomic reduction was the annular ligament. 10 To date, some authors have reported rare cases of irreducible anteromedial radial head dislocation in children caused by the biceps 1 , 2 , 5 , 9 , 11 , 12 and brachialis tendons. 3 , 4 , 8 These authors showed that the pathology causing an irreducible anteromedial radial head dislocation was either the biceps or the brachialis tendon ‘clinging’ to or ‘wrapping’ the radial head.…”
Section: Discussionmentioning
confidence: 99%
“…La fracture de Monteggia n´est pas une lésion fréquente en milieu de traumatologie infantile, seulement 2 à 6,5% des fractures luxation du coude [ 2 ]. Elle est d´une incidence annuelle moyenne de 2,6 cas par an [ 7 , 8 ]. Cette fracture est plutôt l´apanage des enfants de tranche d´âge entre 4 et 10 ans [ 2 , 7 , 9 ].…”
Section: Discussionunclassified